Prioritizing implementation factors of electronic document management system (EDMS) using topsis method: a case study in Iraqi government organizations - Abdulkadhim, H. (Asian Research Publishing Network, 2016)
Taking into consideration a complexity of EDMS implementation process which involves a combination of technological, organizational and users factors, this study explores how EDMS implementation factors can be ranked through these dimensions. This paper begins with an examination of the literature on EDMS implementation studies where a conceptual framework has been derived. The study then adopts the TOPSIS method as the analytical tool that tackles the issue in prioritizing the most desirable factors influencing EDMS implementation project. From the results, the top management support, budgetary, strategic planning, staff training, awareness, resistance to change, IT implementation team, ICT infrastructure, security and privacy/trust, and collaboration are the top-ten important factors for Iraqi government organizations to implement EDMS applications. This paper draws on the research results for implications of IT managerial practice, and then suggests some empirical tactics in order to enhance in managing the EDMS implementation process in government.